ANALISIS KEPUASAN WAJIB PAJAK BERDASARKAN KOMPETENSI FISKUS DAN KUALITAS PELAYANAN (Studi Kasus di Kantor Pajak Pratama Bireuen) - Riyandi, Riyandi; Azhari, Azhari; Mahyu, Danil (Ekonomika : Jurnal Ekonomi dan Pembangunan, 2022)
The research was carried out on taxpayers registered at KPP Pratama Bireuen, with 68 taxpayers as samples using the Slovin formula with incidental sampling. Research instrument with a valid and reliable questionnaire. The results of the multiple linear regression analysis approach show that taxpayer satisfaction is influenced by the competence of the Fiscus and service quality, with a regression model Y = 1.138+ 0.297 X1 + 0.218 X2. The influence of the quality of tax authorities' competence is higher than the quality of service. And the coefficient of determination (R2) is 0.793. Meaning that the contribution of Fiscus competence and service quality is 79.3% to Taxpayer Satisfaction.